Employee Competency and Organizational Culture Adaptation in CNX: Basis for Action Plan - Rosales, Flores Abril P.; Urbina, Marilou C.; Pendon III, Fernando T. (International Journal of Research in Interdisciplinary Studies, 2025)
This study investigates the relationship between employee competency and organizational culture adaptation in CNX, a business process outsourcing (BPO) company located in Nuvali, Laguna. In today’s rapidly evolving service environments, organizational success is increasingly dependent on how well employee skills align with and support cultural adaptability. Using a descriptive-correlational design, this research involved 278 randomly selected CNX employees. A validated researcher-made questionnaire was used to assess employee competency across three dimensions—knowledge, skills, and behavior—and organizational culture adaptation in terms of cultural flexibility, responsiveness, and growth. Data were analyzed using weighted mean, Spearman’s rank correlation, and Kruskal-Wallis test. The findings revealed that employee competency was rated highly in all dimensions (overall WM = 3.43), and so was organizational culture adaptation (overall WM = 3.38). A very high positive correlation (ρ = 0.85, p < 0.01) was observed between the two variables, and a significant impact was identified (χ² = 153.60, p < 0.01), indicating that higher employee competency strongly influences greater cultural adaptability. These results underscore the importance of integrated competency development in promoting a responsive and growth-oriented organizational culture. Based on the findings, a six-point action plan is proposed to enhance employee performance and sustain organizational adaptability. This study contributes to the growing body of knowledge on human resource development and organizational behavior, with implications for BPO firms seeking strategic alignment between workforce capability and cultural transformation.